Flourishing in Resonance: Joint Resilience Building Through Music and Motion - Nijs, Luc; Nicolaou, Georgia (Frontiers in Psychology, 2021)
Worldwide, children face adverse childhood experiences, being exposed to risks ranging from, exposure to political violence and forced migration over the deleterious effects of climate change, to unsafe cultural practices. As a consequence, children that seek refuge or migrate to European countries are extremely vulnerable, often struggling with integration in school, peer community, and their broader social circle. This multifaceted struggle can derive from external factors, such as the adaptation process and contact with other children, or internal factors such as the fears and trauma that every child carries within them since they departed from their homeland . To bounce, grow, connect and create in both adversity and opportunity, children need to build resilience, i.e. the capacity of an individual to maintain stable psychological functioning throughout the course of adversity. On the one hand, building resilience requires developing a set of individual skills (internal protective factors), such as self-control, emotion regulation, self-esteem and agency. On the other hand, building resilience involves developing social skills (external protective factors), connection and close relationships. In this theoretical contribution, we review and map existing research to argue that activities based on the combination of music and movement have a strong potential to intensively build resilience. First, we connect the concepts of resilience and eudaimonia, based on the protective factors and key components of resilience. Then we discuss how music and movement, separately, may contribute to building resilience. Next, drawing on the basic mechanisms of musical sense-making, we argue that through combining music and movement, children engage in empowering musical sense-making processes that support building build resilience, and in this way, support them to grow together and deeply experience eudaimonic values such as self-awareness, confidence and self-esteem, personal autonomy, connection, belonging and bonding. Finally, we connect theory to practice. Based on the presented theoretical elaborations and on the authors’ experience as practitioners, we propose a set of guiding principles for the design of movement-based musical activities that foster the internal and external factors, necessary to build resilience.